Does seed industry innovation in developing countries contribute to sustainable development of grain green production? Evidence from China. (20th June 2023) - Gong, Siyu; Wang, Bo; Yu, Zhigang; Cui, Zhaoda
Abstract: China's seed industry innovation strategy is considered a key measure to guarantee grain green production. However, there has been no scholarly focus on the implementation process in different regional characteristics. This exploration has important reference to bridging the gap between seed innovation in developing and developed countries. In this study, we used the 2012–2021 provincial panel data in China, the two-way fixed effect model, instrumental variable method and least squares method were used to investigate the impact of seed industry innovation on the green total factor productivity of grain with different regional characteristics. The study results show that the seed industry innovation promotes green production of grain. When total factor productivity of grain is decomposed into green technical progress and green technical efficiency, seed industry innovation has a significant positive impact on both of them. This meant that seed industry innovation not only improved the efficiency of green food production but also led to the promotion of green food production technology. In addition, regional resource misallocation inhibited grain green production and acted as a negative moderator for seed industry innovation. In contrast, regional environmental regulation and absorptive capacity act as positive moderators. Finally, we analyzed the heterogeneity of grain functional areas and found that grain main production provinces and grain production and consumption balance provinces had similar conclusions. However, capital misallocation and absorptive capacity did not significantly moderate the impact of seed innovation on green total factor productivity of grain in the gain main consumption provinces.